2010
DOI: 10.1080/13647830903548834
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of the chemistry solver for modeling DI engine combustion using dynamic adaptive chemistry (DAC) schemes

Abstract: Acceleration of the chemistry solver for engine combustion is of much interest due to the fact that in practical engine simulations extensive computational time is spent solving the fuel oxidation and emission formation chemistry. A dynamic adaptive chemistry (DAC) scheme based on a directed relation graph error propagation (DRGEP) method has been applied to study homogeneous charge compression ignition (HCCI) engine combustion with detailed chemistry (over 500 species) previously using an R-valuebased breadth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 32 publications
3
57
0
1
Order By: Relevance
“…It has also been successfully coupled with the DAC scheme and parallelized using a load balancing scheme [18]. It was found in these studies that significant amounts of computational time were saved with the adaptive multigrid chemistry model.…”
Section: Multigrid Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been successfully coupled with the DAC scheme and parallelized using a load balancing scheme [18]. It was found in these studies that significant amounts of computational time were saved with the adaptive multigrid chemistry model.…”
Section: Multigrid Modelmentioning
confidence: 99%
“…This algorithm has been validated on diesel engine simulations and has proven to be very efficient [18,34].…”
Section: Adaptive Load-balancing Algorithm For Parallelizationmentioning
confidence: 99%
“…Accuracy of the CCM method was extensively verified by the authors in [31,45] where it was applied to RANS and DNS non-premixed combustion simulations. To further reduce the CPU time for chemistry integration, the CCM method operates together with the TDAC algorithm [30,32] which combines the ISAT and DAC techniques [41,44,48]. The ISAT algorithm intends to reuse computationally demanding results, e.g.…”
Section: Cpu Time Reductionmentioning
confidence: 99%
“…The efficiency of the graph search algorithm is also an important factor due to the recent use of DRGEP in dynamic skeletal reduction approaches [10][11][12]. In the worst case, DRGEP is applied at every spatial grid location and each time step to generate locally relevant skeletal mechanisms, although as Shi et al [12] demonstrated this can be eased by combining dynamic DRGEP-based reduction with an adaptive multi-grid chemistry model.…”
Section: Introductionmentioning
confidence: 99%
“…Development of this approach has since focused on variants of the method [5][6][7][8], but DRG with error propagation (DRGEP) in particular has received much attention [6,[8][9][10][11][12][13]. The DRGEP differs mainly from DRG in that it takes error propagation down graph pathways into account.…”
Section: Introductionmentioning
confidence: 99%